Ordinance No. 79, §§ 2, 3, & 15, Yakima City Council (1910) (Yakima, Washington). - (:unkn) unknown (General Publisher, 1910)
It shall be unlawfull1 for any person to fire or discharge any pistol, gun, rifle, cannon, or any description of firearms within the corporate limits of said city.It shall be unlawful for any person not being a police officer or not having a permit from the mayor, to carry concealed about his person, any pistol, sling shot, brass or iron nuckle, or other damgerous or deadly weapon."
--
Keywords: CARRY - CONCEALED